Political discourse in Central, Eastern and Balkan Europe - Berrocal, Martina; Salamurović, Aleksandra, 1978- (Discourse Approaches to Politics, Society and Culture,, 2019)
"This edited volume offers new insights into contemporary political discourses in Slavic speaking countries by focusing on discursive and linguistic means deployed in relevant genres, such as parliamentary discourse, commemorative and presidential speeches, mediated communication, and literal and philosophical essays. The depth of the linguistic analysis reflects different levels of linkage between language and social practice constituting the discourse. The theoretical and methodological approaches discussed range from interactional pragmatics over corpus linguistics to CDA. The chapters contain original language material in Russian, Polish, Czech, Croatian, Bosnian and Macedonian, and the authors address issues such as the affiliation to different political and social groups within parliamentary settings, national identity, gender and minorities, as well as cultural memory and reconciliation"--